Scent of a garden : a novel - Patel, Namrata (Lake Union Publishing, 2023)
When her heightened sense of smell disappears, jeopardizing her career, Poppy Patel, a gifted Paris perfumer, returns home to tend to her grandmother's aromatic garden only to discover it has been uprooted and destroyed, while navigating family drama, childhood friendships and a former love to heal an unscented life.